A rare clinical presentation: Adult-onset Still’s disease - Banjade, Prakash; Jaishi, Prakash Poudel; Malla, Jonas (Journal of Kathmandu Medical College, 2020)
Adult -onset Still’s disease (AOSD) is a rare, idiopathic, inflammatory disorder of unknown etiology and pathogenesis that presents in 5 to 10% of patients as fever of unknown origin (FUO )exclusion characterized by generalized migratory joint ache, blanchable rash, fever and other systemic manifestations. We report an interesting case of a 23 year old Nepalese lady from Okhaldunga who presented with one-month duration of FUO along with sore throat, fever, vomiting, generalized joint ache, erythematous blanchable rash, headache and visual impairment. On examination there was hepatomegaly and investigations showed raised liver enzymes, serum ferritin and fibrinogen.After extensive workup, potential differential diagnoses were ruled out She was diagnosed to have Adult -onset Still’s disease based on Yamuguchi criteria after exclusion of other potential differentials.The patient partially responded to prednisolone and later methotrexate was prescribed which improved her symptoms. The case history, incidence, pathogenesis, clinical manifestations, differential diagnoses, diagnostic workup, treatment modalities, and prognosis of AOSD are discussed in this case report.